Modeling of dynamic mechanical properties of epoxy and epoxy-phenolic reinforced with multi wall-carbon nanotubes - Morales Arias, Juan Pablo (2014)
The viscoelastic properties of nanocomposites based on epoxy and epoxy-phenolic blend matrix reinforced with multi wall-carbon nanotubes were studied. It was varied the content of carbon nanotube (0.2 and 0.5 wt.%) and its surface state (pristine vs. oxidized). The characterization of the nanocomposites was done by means of infrared spectroscopy and chemical methods. From the viscoelastic properties of nanocomposites, characteristic properties such as: storage modulus (E0), tan δ and damping peak (tan δ) were obtained. The void content was also determined. Also, weibull statistics are used to represent the failure of secondary bonds during the relaxation processes that lead to stiffness change over the full range of use temperatures. The incorporation of phenolic resin to an epoxy matrix leads to an increase of the relaxation modulus. The glass transition temperature of the epoxy-phenolic nanocomposites decrease when it is incorporated carbon nanotubes, independently of its state (pristine or oxidized).